The Power of Education: Education for All, Development, Globalisation and UNESCO - POWER, Colin (Springer, 2016)
This book is about the power of education: the kind of education that simultaneously improves the quality of life both of individuals and the wider society. It explains why education must be viewed as a basic human right, as a value in and of itself, and reviews the evidence on how education builds the human resources that individuals and nations need to be productive, to continue to learn, to solve problems, to be creative, and to live together and with nature in peace and harmony. When nations ensure that such an education is accessible to all throughout their lives, education becomes the engine of sustainable development – economic, social, moral and cultural. The book is unique in that it covers the development of education at all levels in all countries of the Asia-Pacific region and beyond, using the latest international data bases, while blending in analyses of both quantitate and qualitative research.